(untitled) (Balneo and PRM Research Journal, 2025)
Background: Spinal Muscular Atrophy (SMA) is a rare neurodegenerative disease caused by insufficient synthesis of SMN protein, characterized by progressive muscle weakness, atrophy, and complications affecting the respiratory and digestive systems. Disease severity tends to be greater when symptoms manifest at an earlier age. Since 2016, the FDA-approved drug nusinersen has provided a disease-modifying treatment option. Identifying predictive factors for patient outcomes over time remains essential. Methods: This retrospective study analyzed clinical and biological parameters in 42 patients (ages 13–215 months) with SMA types 2 and 3 over the first three years of nusinersen treatment. We assessed pNF-H levels in CSF and serum—neuronal proteins associated with neurodegeneration—as well as serum creatinine levels, a marker of muscle activity, and motor skill scores to evaluate pNF-H’s potential as a predictor of motor development. Results: Elevated pNF-H levels were associated with a lower SMN2 gene copy number and more recent disease onset. Following nusinersen treatment, pNF-H levels stabilized at low values, likely due to basal metabolic activity. Conclusions: In SMA types 2 and 3, higher baseline CSF pNF-H levels correlated with improved performance over time. Additionally, higher serum creatinine levels and smaller changes in pNF-H during the loading phase or various periods of maintenance treatment were associated with better motor development outcomes at two and three years of treatment.